Skills Needed for Working in the Automated Green Energy Sector - Olek, Krystian; Krzos, Grzegorz (Publishing House of Wroclaw University of Economics and Business, 2024)
[The book aims to present the most critical competencies that employees who want to work or are working in the green energy sector should have. The manual provides a description of the ten most essential competencies necessary to perform work properly in the industry discussed, as well as examples of their practical application in market conditions. The textbook is intended primarily for pupils, students, employees, and entrepreneurs in African countries, but its universality and utilitarian nature allow for its global use.] z zapowiedzi
Olek, K., and Krzos, G. (2024). Skills Needed for Working in the Automated Green Energy Sector. Publishing House of Wroclaw University of Economics & Business.
Keywords: technical skills; business competencies; green energy; sustainable development; renewable energy